Identification of Student Misconception Level Through The Four Tier Dignostic Test as A Result of The Implementation of E-Module Development - Prafitasari, Aulya Nanda; Pipit Candrasari (Science Education and Application Journal, 2024)
Learning in Kurikulum Merdeka guides students not only to wait for information from the teacher, but also to independently obtain good learning resources. Each student's literacy skills will influence their ability to understand material. Students having a misconception still becomes a big threat, therefore the students need specially designed learning media based on materials needed which is listed on the teacher's lesson plan. The learning media was developed in e-modules that can be used both offline and online so as to help reduce misconceptions in the material being studied. This study aims to identify the level of students' misconceptions between classes that use e-modules and those that do not. The research design used a posttest only control group design with questions of the type of four tier diagnostic test. Students answered by google forms and analyzed based on the Certainty of Response Index (CRI) criteria. The results of the implementation of e-modules, that have been developed based on the needs of the teacher's lesson plan, show differences in the level of misconceptions between classes that use it and those who don't. In the experimental class, 33.4% of students stated misconceptions, while in the control class it was 51.7.